2007
DOI: 10.1007/s11244-007-0240-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ageing time on co-precipitated Cu/ZnO/ZrO2 catalysts used in methanol synthesis from CO2 and H2

Abstract: The effect of suspension ageing time during the catalyst precipitation process on the performance of co-precipitated Cu/ZnO/ ZrO 2 catalysts in methanol synthesis from CO 2 and H 2 has been studied. The ageing time influenced greatly the physical and chemical characteristics of the catalysts as well as their activity in the methanol synthesis. Prolonged ageing was advantageous, mainly due to both lower sodium contents and enhanced crystallinity of the catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 15 publications
0
36
0
1
Order By: Relevance
“…Moreover, aiming to further enhance the reactivity of such CZZ systems, different oxide promoters (CeO2, Ga2O3, La2O3, MnO, MgO, etc.) were adopted, and the positive effects of them have also been documented [15][16][17][18][19][20][21][22][23][24][25][26]. Additionally, the composition, texture of catalysts, and dispersion of metal and oxide phases on the catalysts are also greatly associated with their activities, which can be obtained using a variety of preparation methods [16,23,[27][28][29][30][31] Arena et al [16,21,28,32] used reverse co-precipitation under ultrasound irradiation to obtain a series of Cu-ZnO/ZrO2 catalysts with a remarkable total surface area and high dispersion.…”
Section: Open Accessmentioning
confidence: 99%
“…Moreover, aiming to further enhance the reactivity of such CZZ systems, different oxide promoters (CeO2, Ga2O3, La2O3, MnO, MgO, etc.) were adopted, and the positive effects of them have also been documented [15][16][17][18][19][20][21][22][23][24][25][26]. Additionally, the composition, texture of catalysts, and dispersion of metal and oxide phases on the catalysts are also greatly associated with their activities, which can be obtained using a variety of preparation methods [16,23,[27][28][29][30][31] Arena et al [16,21,28,32] used reverse co-precipitation under ultrasound irradiation to obtain a series of Cu-ZnO/ZrO2 catalysts with a remarkable total surface area and high dispersion.…”
Section: Open Accessmentioning
confidence: 99%
“…151,156,163 Catalytic activity and selectivity toward methanol are both improved due to the enhanced copper dispersion in the presence of ZrO 2 . 151,159,160,174,175 In addition, the crystal types of zirconia influence performance of the catalyst. 162,176 For instance, copper species supported on m-ZrO 2 are 4.5 times more active compared to Cu/t-ZrO 2 due to the higher concentration of adsorbed active intermediates (i.e., HCOO and CH 3 O).…”
mentioning
confidence: 99%
“…The results are in comparable with other CO 2 hydrogenation studies carried out on Cu/ ZnO/ZrO 2 catalysts. For instance, Raudaskoski et al (2007) have obtained CO 2 conversions of 3.7-16.7% and 22.0-35.1% selectivity to methanol at 230°C and 30 bar on Cu/ZnO/ZrO 2 catalysts prepared by precipitation method with different ageing time. As depicted above, the CO 2 conversion over the CZAZ catalyst increased progressively with the increase of Cu/Zn molar ratio and it is consistent with the change of the specific surface area, SA BET (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…As depicted above, the CO 2 conversion over the CZAZ catalyst increased progressively with the increase of Cu/Zn molar ratio and it is consistent with the change of the specific surface area, SA BET (Table 1). Several studies have demonstrated that there are two active centers involved in the catalytic process of CO 2 hydrogenation over the Cu/ZrO 2 -based catalysts (Lin et al 2009;Raudaskoski et al 2007;Sloczynski et al 2004;Xiao et al 2015). One is the Cu component, and the other is the so-called 'support' ZrO 2 .…”
Section: Resultsmentioning
confidence: 99%